THE EFFECT OF ONOMATOPOEIA IN COMIC STRIPS AND INSTRUMENTAL MOTIVATION TOWARDS STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Putri, Aulia; Angraini, Yuli; Manurung, Sulastri (JURNAL DIMENSI, 2017)
The aims of the research were to measure a significant effect on students’ average scores of reading comprehension achievement between students:1)who both had high instrumental motivation in experiment class (Onomatopoeia in Comic Strips) and control class;2) who had high instrumental motivation in control class and the ones who had middle instrumental motivation in experiment class;3) who both had middle instrumental motivation in experiment class (Onomatopoeia in Comic Strips) and control class;4) who had high instrumental motivation in experiment class and the ones who had middle instrumental motivation in control class;and 5) to find whether there was an interaction or not on students’ reading comprehension achievement taught using Onomatopoeia in Comic Strips towards instrumental motivation. Experimental with factorial design was used in this research by using 40 samples of the third semester students of English Education Study Program of UNRIKA classified into high and middle instrumental motivation. The validity used content validity while reliability of the data measured by Cronbach Alpha using SPSS 24. The data were collected through Onomatopoeia test and Gardner’s instrumental motivation questionnaire. It was found from the analysis that both of the data were normal, homogenous and all hyphoteses had a significant effect. Keywords: Onomatopoeia in Comic Strips, Instrumental Motivation, Reading